Exploring the role of corrective feedback in helping Grade 8 learners to improve the accuracy of their written English: an action research case study - Miranda, Zoachina Nangobe (Rhodes University, Faculty of Education, Department of Education, 2016)
This action research study explored and analysed the role of teacher corrective feedback in helping Grade 8 learners to improve the accuracy of their written English as their second language. Therefore, the goals of this study were to examine the kind of language errors my grade 8 learners' made in their writing, to find out whether these errors could be categorized linguistically, and to determine if they were errors, mistakes or lapses. The study further analysed how learners responded to my feedback, and also determined which feedback strategies worked best to help my learners deal with their errors, mistakes or lapses. This study set out to look at six learners from one Grade 8 class of 40 learners. The data were gathered from six written essay scripts, and each learner wrote four essay draft revisions. The learners' written essays were analysed by means of checklists in order to identify the types and patterns of errors made. Errors such as punctuation, past tense verbs, spelling and vocabulary were identified, analysed and categorized to provide insights into reasons underlying the instances in which they were committed. The findings of this study showed that factors underlying learners' written errors included mother-tongue interference, overgeneralization, fossilization, translation, lack of concentration, and carelessness. The findings further showed that corrective feedback on learners' draft revisions provided them with extensive exposure and practice in English, enabled them to internalize language rules, and reduced the tendency to commit errors in their writing. The findings further suggest that procedures such as multiple-draft activities, indirect feedback, direct feedback, focused corrective feedback, error correction and written feedback with explicit corrective comments improved their levels of writing. Furthermore, putting these procedures into practice and reflecting critically on how to apply them helped enrich my own teaching practices and development in relation to the provision of corrective feedback to improve accuracy in learners' writing. The findings are discussed in the context of the related literature. This study should be read by ESL teacher-trainers, ESL teachers, ESL student-teachers and ESL learners/students in general.
Keywords: Uncatalogued